2021
DOI: 10.3390/toxins13050334
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Synbiotic Formulation Decreases Free Serum Indoxyl Sulfate, Small Intestine Permeability and Ameliorates Gastrointestinal Symptoms in a Randomized Pilot Trial in Stage IIIb-IV CKD Patients

Abstract: Proteolytic dysbiosis of the gut microbiota has been recognized as both a typical feature of chronic kidney disease (CKD) and a risk factor for its progression. Blood accumulation of gut-derived uremic toxins (UTs) like indoxyl sulfate (IS) and p-cresyl sulfate (PCS), intestinal permeability and constipation are typical features accompanying CKD progression and triggering chronic inflammation. In order to verify the efficacy of the innovative synbiotic formulation NATUREN G® in modulating the levels of circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…The glomerular filtration rate was improved significantly in patients who were on the low-protein diet combined with prebiotics and probiotics [ 35 ]. Similar results were drawn from the other two clinical controlled trials on the probiotic intakes that were associated with a decline in the progression of CKD [ 13 , 36 ].…”
Section: Effect Of Probiotics In Advanced Stage Of Ckd (Stage 3–5nd)supporting
confidence: 83%
See 1 more Smart Citation
“…The glomerular filtration rate was improved significantly in patients who were on the low-protein diet combined with prebiotics and probiotics [ 35 ]. Similar results were drawn from the other two clinical controlled trials on the probiotic intakes that were associated with a decline in the progression of CKD [ 13 , 36 ].…”
Section: Effect Of Probiotics In Advanced Stage Of Ckd (Stage 3–5nd)supporting
confidence: 83%
“…Most of the probiotics used in the studies were mixed formulation, accounting for 80% of the total. Multiple probiotic products are now marketed and the efficacy, safety, and tolerance were shown in some trials [ 11 , 12 , 13 ].…”
Section: Overview Of Probiotics Used In Ckdmentioning
confidence: 99%
“…Four studies [ 15 , 18 , 20 , 23 ] were involved in the assessment of effects of probiotics on serum creatinine in non-dialysis patients and no statistically significant difference was found [SMD = −0.26; 95%CI: (−0.96, 0.44); p = 0.46] with a high heterogeneity (I 2 = 82%) ( Figure 3(A) ). Both prebiotics subgroup [ 21 , 22 , 25 ], [SMD = 0.22; 95%CI: (−0.13, 0.57); p = 0.21; I 2 = 6%] and synbiotics subgroup [ 16 , 17 , 19 , 24 , 26 ], [SMD = 0.15; 95%CI: (−0.16, 0.46); p = 0.34; I 2 = 40%] did not show a significant decrease in serum creatinine level ( Figure 3(B,C) ). The heterogeneity of the SMDs was considered low in prebiotics subgroup and synbiotics subgroup.…”
Section: Resultsmentioning
confidence: 99%
“…The heterogeneity of the SMDs was considered high. Eight RCTs [ 15 , 17 , 19 , 20 , 22 , 24–26 ] with biotic intervention longer than 2 months also showed no significant difference in their meta-analysis [SMD = 0.17; 95%CI: (−0.03, 0.38); p = 0.10; I 2 = 17%] ( Figure 4(B) ). Heterogeneity was removed with a duration more than 2 months.…”
Section: Resultsmentioning
confidence: 99%
“…In the synbiotic group, a reduction in zonulin level was observed, together with the increased variety of the gut bacteria. A recent study showed that NATUREN G ® synbiotic can reduce intestinal permeability in patients with chronic kidney disease [ 165 ]. Two-month intake of synbiotics resulted in positive changes in the intestine, including a reduction of abdominal pain, constipation syndrome and small intestinal permeability.…”
Section: Synbioticsmentioning
confidence: 99%